Market concentration, diversification, and financial distress in the Indonesian banking system - Farida Titik Kristanti; Deannes Isynuwardhana; Sri Rahayu (University of Merdeka Malang, 2019)
The economic theory provides conflicting predictions about the relationship between the market structure of the banking industry and financial distress. The view of